2006
DOI: 10.1016/s1359-6446(05)03668-8
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing in vivo siRNA delivery for drug discovery and therapeutic development

Abstract: The use of RNA interference (RNAi) is spreading rapidly to nearly every aspect of biomedical research. The gene silencing capability of RNAi is being used to study individual gene's biological function and role in biochemical pathways. However, the efficacy of RNAi depends upon efficient delivery of the intermediates of RNAi, short interfering RNA (siRNA) and short hairpin RNA (shRNA) oligonucleotides. The delivery challenge is even greater when the aim is to inhibit the expression of target genes in animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 49 publications
(65 reference statements)
1
106
0
Order By: Relevance
“…In vivo siRNA delivery remains challenging due to the poor stability of unmodified siRNA molecules and the difficulty in delivering them intracellularly. 20,22 It was shown that polyethylenimine (PEI) could protect siRNA from enzymatic and nonenzymatic degradations and efficiently deliver them into target cells in culture. 23,24 Moreover, it was shown that PEI can also efficiently deliver siRNA complexed with it to tumors in mice after systemic administration.…”
Section: More Importantly a Higher Levelmentioning
confidence: 99%
“…In vivo siRNA delivery remains challenging due to the poor stability of unmodified siRNA molecules and the difficulty in delivering them intracellularly. 20,22 It was shown that polyethylenimine (PEI) could protect siRNA from enzymatic and nonenzymatic degradations and efficiently deliver them into target cells in culture. 23,24 Moreover, it was shown that PEI can also efficiently deliver siRNA complexed with it to tumors in mice after systemic administration.…”
Section: More Importantly a Higher Levelmentioning
confidence: 99%
“…In particular, small interfering RNAs (siRNAs), 21-23 nucleotide-length fragments (Elbashir et al 2001;Hannon 2002;Xie et al 2006), have been shown to be of great value in decreasing the expression of the target gene by in vivo administration (Song et al 2003;Nakamura et al 2004;Schiffelers et al 2005;Khoury et al 2006) In the present study, we applied siRNA targeting to an OPN coding sequence (OPN-siRNA) to inhibit OPN function by reducing OPN expression. We demonstrate the remarkable efficacy of OPN-siRNA to prevent EAU in mice.…”
Section: Introductionmentioning
confidence: 99%
“…11 Different complementary approaches are currently developed in rodents to increase the in vivo stability of the siRNA molecule, to target it to the correct tissue and to facilitate its cellular uptake. These include chemical modification of the silencing RNA 10 packaging into protective particles 12,13 and conjugation to cellspecific ligands or antibodies. 14,15 Nevertheless, the further use of siRNA as therapeutic molecules will mostly rely on the development of efficient in vivo delivery methods, which remains by far the major challenge in this field.…”
Section: Introductionmentioning
confidence: 99%